Persepsi Petani Terhadap Penerapan Good Agricultural Practice (GAP) pada Komoditas Padi di Desa Rukam Kecamatan Mendo Barat - Ulfa, Febriyanti Putri; Mustamid, Mustamid; Syahadan, Syahadan; R, Amri; Mustikarini, Eries Dyah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Sustainable agriculture plays a crucial role in improving food security by efficiently and environmentally friendly means of meeting food needs. In Indonesia, rice is a vital staple food source and source of livelihood for the majority of rural residents. However, conventional agricultural practices, which rely heavily on chemical fertilizers, synthetic pesticides, and excessive land exploitation, have led to various environmental and social problems. Consequently, farmers' understanding and perceptions of the concept of sustainable agriculture remain largely unknown. This study aims to determine rice farmers' perceptions of sustainable agriculture through the application of Good Agricultural Practice (GAP) and to identify factors influencing their perceptions. The study was conducted in Rukam Village, Mendo Barat District, from September to November 2025. A survey method was used, with 30 rice farmers as respondents, using purposive sampling. Data were analyzed descriptively to determine farmers' perceptions, and quantitatively using multiple linear regression to analyze factors influencing farmers' perceptions. The analysis showed that farmers' perceptions of GAP implementation in lowland rice were categorized as very good, with a percentage of 81.88%, covering economic, social, and technical aspects. The results of multiple linear regression are Y = 12.814746 – 0.331873 X1 – 0.407773 X2 + 0.527081 X3 + 0.340421 X4. The variables of education and extension workers have a significant effect on farmers' perceptions in the implementation of GAP for rice commodities, while the variables of farming experience and cultivation techniques do not have a significant effect on farmers' perceptions in the implementation of GAP for rice commodities.